Physiopathology and impact of iron deficiency and anemia in the pregnant women and newborn/infant - Milman, Nils (2013)
Iron deficiency is the most prevalent deficiency disorder and iron deficiency anemia the most frequent form of anemia in pregnant women. Minor causes of anemia are folate and vitamin B12 deficiency, hemoglobinopathy and hemolytic anemia. Anemia is defined as hemoglobin <110 g/L in 1st and 3rd trimester and <105 g/L in 2nd trimester. The diag nosis relies on analysis of hemoglobin, a full blood count and plasma ferritin, which can be supported by plasma transferrin saturation and serum soluble transferrin receptor (sTfR). Among non-pregnant women of reproductive age, 40% have ferritin below 30 μg/L, which indicates small or absent iron reserves and therefore a poor iron status with respect to future pregnancy. Requirements for absorbed iron increase during pregnancy from 0.8 mg/day in 1st trimester to 7.5 mg/day in 3rd trimester, on the average 4.4 mg/day. Among women of reproductive age, 40% of Scandinavian and possibly up to 80% of Peruvian women (depending of social status and residence) have a poor iron status with respect to future pregnancy. In Peru, the prevalence of anemia in non-pregnant women of reproductive age is 22%, and in pregnant women 27%. The prevalence of anemia in the 3rd trimester may vary from 14 to 52% in women not taking iron supplements (depending on country and social status) and from 0 to 25% in women taking iron supplements (depending on the dose of iron). Iron deficiency and anemia has severe implications for pregnant women, being associated with decreased work capacity, fatigue, weakness and psychic dysfunctions, which all impair the quality of life both on the physical and psychical level. In the fetus/newborn infant iron deficiency may have serious consequences for development of brain functions. It increases the prevalence of premature birth and the frequency of low birth weight as well as the perinatal mortality. Children born to iron deficient mothers have poorer cognitive, motor, socialemotional and neurophysiologic development and lower intelligence quotient than infants and children born to iron-replete mothers. Iron deficiency anemia has serious consequences for both women and fetus/newborn infants and requires efficient intervention with iron prophylaxis and/or treatment. In the future, more efforts should be dedicated by the antenatal care health system to eradicate this significant problem.Key words: anemia; iron deficiency; pregnancy